2022
DOI: 10.1111/sltb.12896
|View full text |Cite
|
Sign up to set email alerts
|

Thematic analysis and natural language processing of job‐related problems prior to physician suicide in 2003–2018

Abstract: Introduction:Although previous studies have consistently demonstrated that physicians are more likely than non-physicians to experience work-related stressors prior to suicide, the specific nature of these stressors remains unknown. The current study aimed to better characterize job-related problems prior to physician suicide. Methods:The study utilized a mixed methods approach combining thematic analysis and natural language processing to develop themes representing death investigation narratives of 200 physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Furthermore, Twitter is an ideal microblogging social media site for analysis of naturally occurring data to examine how suicide is talked about during COVID-19 pandemic, as users can upload messages of up to 280 characters of text, also referred to as “tweets”. Previous studies have found natural language processing techniques and such social media analyses to be a feasible and novel method to study public sentiment and emotional manifestations occurred on a given topic [ 15 , 16 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Twitter is an ideal microblogging social media site for analysis of naturally occurring data to examine how suicide is talked about during COVID-19 pandemic, as users can upload messages of up to 280 characters of text, also referred to as “tweets”. Previous studies have found natural language processing techniques and such social media analyses to be a feasible and novel method to study public sentiment and emotional manifestations occurred on a given topic [ 15 , 16 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study investigating work-related tweets using Twitter reported that tweets containing words such as “life” and “need” were included regardless of the emotion expressed in the tweet [ 25 ]. Another study that used NLP to investigate work-related suicides in the National Violent Death Reporting System database identified factors such as mental health issues and conflicts in relationships as preceding factors of suicide [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, while only 2.1% of suicides among those working in protective services were listed on the death certificate as work-related suicide, the cause of death was cited in 15.2% of death investigations of the same group, indicating that work-related suicides were much higher than documented ( Peek-Asa et al, 2021b ). In another study of physician suicides in the USA between 2013 and 2018, examined by integrating natural language processing and thematic analysis, five themes were identified in work-related physician suicides: inability to work due to poor physical health, substance use that compromises employment, the interaction between mental health and work-related issues, legal issues leading to work-related stress, and increased financial stress ( Kim et al, 2022 ). Work-related suicides in the United States increased by 22.2% between 1995 and 2010, becoming one of the country’s leading causes of death.…”
Section: Introductionmentioning
confidence: 99%